Evaluating the influence and modification for environment and sustainability learning outcome in environmental engineering course during Covid-19 pandemic - Nurmin Bolong; Ismail Saad (Researchgate, 2022)
The pandemic has influenced most of us either directly or indirectly. In ensuring the education is always in line with the National Education Philosophy in developing holistic, entrepreneurial, and balanced graduates, the Civil Engineering Program of Universiti Malaysia Sabah utilizes the UMS-OBE system, particularly in course outcome (CO) input to the program outcomes (PO) in the assessment and reporting of student’s performance. As the main stakeholders, learners and lecturers must be actively engaged in the rationale and motivation of implementing the OBE mechanisms. Hence this paper evaluated the course learning outcome and measured their perceptions by categorizing the ranked perception feedback on project-based learning (PBL). This paper highlights the modification in implementing PBL that previously involved physical work on-site. Due to the movement control order (MCO) enforced due to the covid-19 pandemic, the course assessment targeted to instill the program outcome (PO) of Environment and Sustainability attribute was strategized into 3 phases. The analysis found that the course outcome has been successfully achieved, even though a slight decrease was observed from the previous regular face-to-face mode. A slight decrease was observed in the overall grade achievement and course outcome analysis. The instructional modification and intervention in Project-Based-learning to improve online learning strategies, despite the requirement for engineering community fieldwork through the learner’s feedback responses during the three phases in model strategies for course outcome pedagogy, have shown optimistic input by learners and has continuously engaged them through the Project-based-Learning completion